Selected individual determinants of cereal, fruit and vegetable consumption among menopausal women in view of potential health risks - Gacek, Maria (Menopause Review/Przegląd Menopauzalny, 2013)
The aim of this study was to analyze some personal determinants of cereal, fruit and vegetable consumption in a group of menopausal women. We analyzed selected individual characteristics, such as the level of general self-efficacy, optimism, and satisfaction with life. The study, using a questionnaire assessing the frequency of food product consumption and psychological scales (GSES, LOT-R, SWLS), included 320 women aged between 45 and 55 years. Statistical analysis of the Spearman’s rank coefficients of correlation revealed that increased BMI was associated with a significantly higher frequency of white bread consumption (p < 0.05), and decreased consumption of brown rice, whole grains (p  < 0.01), wholegrain noodles, oat meal (p < 0.05), raw and green vegetables (p < 0.01), and fruits, including citruses (p < 0.01). The level of self-efficacy correlated positively with the consumption frequency of white rice (p < 0.05), noodles, raw, cooked, and green vegetables (p < 0.01), and fruits, including citruses (p < 0.01). The level of optimism was positively correlated with the frequency of brown rice, noodle, whole grain and oat meal consumption (p < 0.01). Higher levels of satisfaction with life were associated with more frequent consumption of brown rice, noodles, whole grains, oat meal (p < 0.01), and cooked vegetables (p < 0.05), as well as with a lower frequency of white bread consumption (p < 0.05). The tendencies documented in the correlation analysis were further confirmed by intergroup comparisons with the Kruskal-Wallis and Dunn tests (p < 0.05). Our study revealed that the frequency of selected cereal, fruit and vegetable consumption varies depending on individual characteristics, with a tendency to more rational nutritional choices among women with higher levels of self-efficacy, optimism and satisfaction with life.